Master-Slave Synchronization in Off-Grid Solar Microgrids: Genset and Inverter Configurations - IGNATIUS RIYADI MARDIYANTO; MUSRINAH MUSRINAH; SRI PARYANTO MURSYID; SRI UTAMI; WILDAN ARASSID; RIDWAN NURDIN; AGOENG HARJATMO RAHARDJO; TJATUR UDJIANTO; APIP PUDIN (Institut Teknologi Nasional, Bandung, 2026)
The research analyzes the synchronization performance of off-grid solar AC microgrids by comparing genset-based and inverter-based master-slave configurations. Stability and power quality evaluations were conducted through MATLAB/Simulink simulations and experimental validation. Test results show that the genset-master configuration produces stable synchronization (220V/50Hz), while the inverter-master configuration experiences initial voltage instability. However, by optimizing the power capacity ratio between the master and slave units to 10:1 and implementing a properly designed PWM modulation, the system successfully achieves stable operation. An IoT-based monitoring system using ESP32 and PZEM-004T sensors provides real-time data to validate these findings, confirming that while the inverter-based master configuration is feasible, precise design parameters are required to ensure reliable synchronization